Effect of Virtual Reality-Based Interventions on Pain During Wound Care in Burn Patients; a Systematic Review and Meta-Analysis - Norouzkhani , Narges; Chaghian Arani , Raziyeh; Mehrabi, Hamidreza; Bagheri Toolaroud , Parissa; Ghorbani Vajargah , Pooyan; Mollaei , Amirabbas; Hosseini , Seyed Javad; Firooz, Mahbobeh; Falakdami , Atefeh; Takasi , Poorya; et al. (Archives of Academic Emergency Medicine, 2022)
Introduction: Burn patients undergo daily painful wound care procedures, including washing, debridement, and dressing. This systematic review and meta-analysis aimed to examine the effect of virtual reality (VR)-based interventions on pain during wound care in burn patients. Methods: A comprehensive systematic search was conducted on international electronic databases such as Scopus, PubMed, and Web of Science with keywords extracted from Medical Subject Headings such as "Virtual reality", "Virtual reality therapy", "Virtual reality exposure therapy", "Virtual reality immersion therapy", "Exergaming”, “Active-video gaming”, “Burns”, “Wound healings”, “Pain”, and “Pain management” from the earliest to May 6, 2022. The Joanna Briggs Institute (JBI) critical appraisal checklist was used to assess the quality of randomized control trials and quasi-experimental studies. Results: 1,293 patients with burns were included in 30 studies, and their mean age was 22.89 (SD=7.63) years. 70.72% of the participants were male, and 67.05% were in the intervention group. This meta-analysis showed that VR significantly decreased pain severity in the intervention group compared to the control group (standard mean difference (SMD): -0.70, 95%CI: -0.97 to -0.43, Z=5.05, P<0.001, I2:82.0%). Immersive VR intervention showed statistically significant effects in reducing pain intensity among the intervention group, compared to the control group (SMD: -0.73, 95%CI: -0.97 to -0.49, Z=5.88, P<0.001, I2:69.3%); however, this finding was not the same for non-immersive VR (SMD: -0.62, 95%CI: -1.43 to 0.19, Z=1.51, P=0.132, I2:91.2%). Conclusion: It is suggested that health policymakers and managers equip burn wards with immersive VR devices to provide the basis for this intervention when caring for patients with burn wounds.